We can use the Boyle’s law in order to solve the problem. We know that pressure is inversely proportional to the volume of the gas. Having said that, the expression can be written as:

`(P_1)*(V_1) = (P_2)*(V_2) `

Where:

`P_1` = 822 Torr

`P_2` = 4110 Torr

`V_1` = 17.0...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We can use the Boyle’s law in order to solve the problem. We know that pressure is inversely proportional to the volume of the gas. Having said that, the expression can be written as:

`(P_1)*(V_1) = (P_2)*(V_2) `

Where:

`P_1` = 822 Torr

`P_2` = 4110 Torr

`V_1` = 17.0 L

`V_2` = ?

Substitute the values and solve for `V_2`

`(P_1)*(V_1) = (P_2)*(V_2)`

`V_2 = (P_1*V_1)/(P_2) `

`V_2 = (822*17.0)/(4110) `

`V_2 = 3.40 L` -> answer

The final volume (`V_2` ) should decrease because the applied pressure (`P_2` ) increases.